2020
DOI: 10.1038/s41598-020-70985-0
|View full text |Cite
|
Sign up to set email alerts
|

The value of adjuvant chemotherapy in stage II/III colorectal signet ring cell carcinoma

Abstract: This study aimed to assess the benefit of postoperative adjuvant chemotherapy in stage II-III colorectal signet ring cell carcinoma (SRCC). Qualified postoperative patients were extracted from Surveillance, Epidemiology, and End Results (SEER) database from 2004 until 2015. We collected 1675 patients in the research, and 936 patients were subjected to adjuvant chemotherapy group. the proportions of married status, male, rectal cancer, grade iii/iV, AJcc stage iii and radiotherapy were higher; While, the rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…Similarly, Zhuang Z et al analyzed 1675 stage II/III colorectal SRCC patients. They concluded that age < 65, tumor size ≤ 5 cm, AJCC stage II, radiotherapy, and chemotherapy were associated with better CSS in colorectal SRCC patients (Zhao et al 2020 ). Studies have shown that tumor TNM stage was closely related to colorectal tumor prognosis (Mlecnik et al 2023 ; Sun et al 2022 ; Delattre et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Zhuang Z et al analyzed 1675 stage II/III colorectal SRCC patients. They concluded that age < 65, tumor size ≤ 5 cm, AJCC stage II, radiotherapy, and chemotherapy were associated with better CSS in colorectal SRCC patients (Zhao et al 2020 ). Studies have shown that tumor TNM stage was closely related to colorectal tumor prognosis (Mlecnik et al 2023 ; Sun et al 2022 ; Delattre et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In CRC, MSI-H, or mismatch repair deficient (dMMR), is a well-established prognostic biomarker for better survival in SRCC patients with localized cancer stages, but SRCC is associated with shorter survival compared with other CRC patients ( 8 , 10 ). It was reported that undefined postoperative adjuvant chemotherapy improved survival time in 936 stage II–III patients ( 19 ). The patient in this case underwent routine chemotherapy postoperatively according to a previous report that SRCC benefitted comparably from adjuvant fluorouracil-based chemotherapy compared with AC ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…found that adjuvant fluorouracil-based chemotherapy for stage III colon cancer yielded similar benefits for the conventional and SRC subtypes. A recent study including 1,675 patients with stage II/III colorectal SRCC showed that postoperative chemotherapy was an independent prognostic factor for better CSS and OS (CSS: HR = 0.719, 95% CI 0.612–0.844, p < 0.001); (OS: HR = 0.618, 95% CI 0.537–0.713, p < 0.001) [ 84 ].…”
Section: Treatmentmentioning
confidence: 99%